Modelling of blood flow as extended korteweg-de vries and extended korteweg-de vries burgers equation - Siti Sarahanim Saad, 1989-; Mukheta Isa; Fakulti Sains (2013)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2013